The Changes in the Conception of the Relation between Politics and Science: from Weber to Habermas - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2001)
The article seeks to demonstrate the changes in the conception of relations between science and politics in the 20 th century German tradition of social philosophy. This tradition encompasses Max Weber, Karl Mannheim, Frankfurt School and Jürgen Habermas. The analysis of their works revealed that Weber’s neutral attitude towards the political role of science had experienced couple of transformations. First, Weber’s idea of science as a political instrument was radicalized in Mannheim’s sociology of knowledge. In the latter science as an institution is conceived much more positively because it can replace politics by controllable administration. Second, Frankfurt School denies the mannheimian optimism stressing the negative consequences of that substitution: scientific rationalism invades social and political life at the same time ignoring qualitative aspects that are so important in political field. And, finally, trying to breakthrough the one-sided negativism of elder colleagues in Frankfurt School, Habermas restores weberian attitude towards instrumental character of science. In order to elude the dominance of science two steps are of crucial importance: repoliticization of public sphere and removing restrictions on communication.